Potential of carbon dioxide spraying on the properties of 3D concrete printed structures - Yi Wei Daniel Tay; Sean Gip Lim; Bandar A. Fadhel; Issam T. Amr; Rami A. Bamagain; Ali S. Al-Hunaidy; Suvash Chandra Paul; Ming Jen Tan (Carbon Capture Science & Technology, 2024)
Achieving net carbon neutrality is a global goal toward mitigating climate change presumed consequences. The building and construction sector, responsible for approximately 40 % of greenhouse gas emissions, requires innovative zero-carbon technologies. This paper investigates the synergistic potential of combining 3D concrete printing (3DCP) and carbon capture and sequestration (CCS) to advance net carbon neutrality in construction. By implementing different CO2 spraying regimes, this study demonstrates improved carbon dioxide (CO2) uptake and the crystallinity of precipitated calcium carbonate (CaCO3). The findings indicate that the method's effectiveness heavily relies on appropriate printing parameters and curing conditions. Chamber-cured samples exhibit the highest CO2 uptake but the lowest mechanical strength, while ambient-cured samples show the opposite trend. It is also important to note that the duration of CO2 exposure in this study was relatively short, resulting in limitations in both CO2 uptake and strength gain. Nevertheless, this study highlights the potential of synergistically combining 3DCP and CCS technologies for net carbon neutrality, emphasizing the critical role of the construction sector in achieving global emission reduction targets.